455 Proton Beam Therapy in Rectal Cancer: A Systematic Review and Meta-Analysis. (4th May 2021) - Fok, M; Toh, S; Maducolil, J E; Fowler, H; Clifford, R; Parsons, J; Vimalachandran, D
Abstract: Introduction: Radiotherapy for locally advanced rectal cancer is conventionally performed using photon-based radiotherapy (PBR), carrying significant risk of toxicity to organs at risk (OAR). Proton beam therapy (PBT) potentially delivers equivalent dosimetric radiation to the targeted tissue with improved sparing of OAR. We aimed to compare dosimetric irradiation of OAR for PBT versus PBR in patients with rectal cancer and assess any oncological outcomes. Method: An extensive electronic literature search was performed from inception till April 2020 and subsequent meta-analysis performed. Results: Six articles met the inclusion criteria. Dosimetric data of irradiation delivered to OAR for PBT and PBR were calculated for the same patients. PBT had significantly less irradiated small bowel compared to 3DCRT and IMRT, (MD -16.95, 95% CI [-24.03, -9.88], p < 0.00001) and (MD -6.96, 95% CI [-12.99, -0.94], p = 0.02) respectively. Similar results were observed for bladder and pelvic bone marrow. Two studies reported clinical and oncological results for PBT in recurrent rectal cancer with overall survival reported as 43% and 68%. Conclusions: Dosimetric treatment plans have less irradiation of OAR for rectal cancer with PBT compared to PBR. There is a need for further research in PBT and rectal cancer, as promising results have been shown in recurrent rectal cancer.